PELATIHAN PEMBUATAN SITASI DAN DAFTAR PUSTAKA KARYA TULIS ILMIAH MAHASIWA FEBI IAIN TERNATE MENGGUNAKAN MENDELAY - Sudirman, Muh Sajjaj; Usmayani, Ilham Putra (Institut Agama Islam Negeri Ternate, 2023)
Writing scientific papers is very important in the academic world to improve quality and quality for students in making citations and bibliography. Community service in the form of training on making citations and bibliography of scientific papers is carried out to provide knowledge and use of the Mendeley application as a software or reference manager to make references and reference lists easier, practical and accurate. This activity is carried out using the training method with lecture techniques, providing training and direct guidance to students. Participants in the training activities in this PkM were students of the Sharia Banking Study Program, the Sharia Management Study Program, the Shariah Accounting Study Program and the Islamic Economics Study Program, Faculty of Islamic Economics and Business, IAIN Ternate, with a total of 30 participants. The purpose of this activity is that students are expected to be able to independently manage references well. The survey results show that this training is very beneficial for students. This is evidenced by the information provided by students through questionnaires distributed. Based on the results of the questionnaire, it was found that students' knowledge and skills in utilizing the Mendeley application increased.Keywords: Training; Mendeley Application; Students.